Subtask-Based Usability Evaluation of Control Interfaces for Teleoperated Excavation Tasks - Takumi Nagate; Hikaru Nagano; Yuichi Tazaki; Yasuyoshi Yokokohji (Robotics, 2024)
This study aims to experimentally determine the most suitable control interface for different subtasks in the teleoperation of construction robots in a simulation environment. We compare a conventional lever-based rate control interface (“Rate-lever”) with two alternative methods: rate control (“Rate-3D”) and position control (“Position-3D”), both using a 3D positional input device. In the experiments, participants operated a construction machine in a virtual environment and evaluated the control interfaces across three tasks: sagittal plane excavation, turning, and continuous operation. The results revealed that “Position-3D” outperformed others for sagittal excavation, while both “Rate-lever” and “Rate-3D” were more effective for turning. Notably, “Position-3D” and “Rate-3D” can be implemented on the same input device and are easily integrated. This feature offers the possibility of a hybrid-type interface suitable for operators to obtain optimized performance in sagittal and horizontal tasks.